2021
DOI: 10.1097/brs.0000000000004184
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in Reoperation Rates for Adjacent Segment Disease (Operative Adjacent Segment Disease) in Posterior Cervical Fusions Stopping at C7 Versus T1/T2

Abstract: Study Design. A retrospective cohort study with chart review. Objective. To determine whether there is a difference in reoperation rates for adjacent segment disease ([ASD] operative ASD) in posterior cervical fusions (PCFs) that stop at -C7 versus -T1/T2. Summary of Background Data. There are surgical treatment challenges to the anatomical complexities of the cervicothoracic junction. Current posterior cervical spine surgery is based on the belief that ASD occurs if fusions are stopped at C7 although there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Prior clinical studies have shown conflicting results when comparing the extent of multilevel PCF constructs 4–7,16–20. Osterhoff et al5 showed no difference in radiographic outcomes in a retrospective analysis comparing posterior constructs ending at C7 versus T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior clinical studies have shown conflicting results when comparing the extent of multilevel PCF constructs 4–7,16–20. Osterhoff et al5 showed no difference in radiographic outcomes in a retrospective analysis comparing posterior constructs ending at C7 versus T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy remains regarding how caudal to extend a multilevel PCF construct. From a clinical perspective, conflicting outcomes have been reported between multilevel constructs ending at C7 and those crossing the cervicothoracic junction 4–7,16–20. A retrospective review demonstrated constructs ending at C7 are over 2 times more likely to require a revision than constructs ending at T1 at a mean follow-up of over 4 years 4.…”
mentioning
confidence: 99%
“…Patients who underwent fusions into the thoracic spine did have more blood loss and longer operative time. Similarly, in a retrospective cohort study with a 4-year follow-up, Guppy et al did not identify a difference in reoperation rates for adjacent segment disease 4 or pseudarthrosis 5 when cervical fusions were stopped at C7 or T1/T2. In the absence of extenuating factors, stopping at C7 may be a reasonable option given the lower morbidity and complication rate, although further work is needed in this area.…”
Section: Spondylotic Cervical Myelopathymentioning
confidence: 93%
“…They also reported significantly higher rates of wound dehiscence and infection when crossing the CTJ. Similarly, Guppy, et al 56 recently performed a retrospective review of patients undergoing posterior cervical fusion to determine if there was a difference in reoperation rates for ASD when ending constructs at C7 versus T1/T2. They report no difference in operative ASD when stopping at C7 versus T1/T2 in a cohort of 875 patients.…”
Section: Complications Failure Rates and Outcomesmentioning
confidence: 99%